Chiral Phosphorus–Olefin Ligands for the RhI‐Catalyzed Asymmetric Addition of Aryl Boronic Acids to Electron‐Deficient Olefins. Issue 10 (18th April 2016) - Chen, Qian; Li, Liang; Zhou, Guangli; Ma, Xiaoli; Zhang, Lu; Guo, Fang; Luo, Yi; Xia, Wujiong
Abstract: New chiral phosphorus–olefin hybrid ligands derived from the rigid "privileged"l ‐proline have been conveniently prepared and applied in the rhodium‐catalyzed asymmetric arylation of electron‐deficient olefins with arylboronic acids at room temperature; this reaction provides the desired products in excellent yields and high enantioselectivities. The origin of observed stereoselectivity has been investigated by density functional theory (DFT) calculations. Abstract : New chiral phosphorus–olefin hybrid ligands derived froml ‐proline have been conveniently prepared and applied in the rhodium‐catalyzed asymmetric arylation of electron‐deficient olefins with arylboronic acids at room temperature. This reaction provides the desired products in excellent yields with high enantioselectivity. The origin of observed stereoselectivity has been investigated by density functional theory (DFT) calculations.